Colheita de líquido cefalorraquidiano em cães: modificação de técnica prévia - Velasque Gama, Fernanda Gomes; de Oliveira, Fabricio Singaretti; Guimaraes, Gregorio Correa; Rosato, Paula Nunes [UNESP]; Santana, Aureo Evangelista [UNESP] (Universidade Estadual de Londrina (UEL), 2009)
Unlike the already described techniques, which are based on imaginary lines among extremities or bone projections, this research describes a collection technique modification of cerebrospinal fluid (CSF) in dogs, in the atlantooccipital space. The palpation of bone structures in this joint, plus the supported directioning of the needle, does make the collection easy, even by professionals which have no experience in this kind of procedure. The applied technique enabled the collection of adequate volumes of limpid and colorless CSF of 50 healthy dogs in the first attempt of collection. There was no contamination with blood during the procedure, what made possible the correct interpretation of laboratory parameters usually examined in CSF samples.
Cerebrospinal fluid collection in dogs: modification of previous technique
Keywords: Dog; Nervous system; fluid